Taking Others' Perspectives Enhances Situation Awareness in the Smart Home Interface - Yu, Sanghyeong; Han, Kwanghee (Frontiers in Psychology, 2019)
In the smart home environment, all devices are connected to each other and are shared by co-users living together. This may make people’s interactions with the devices more complicated, owing not only to the difficulty of meeting each co-user’s tastes with respect to how the devices operate, but also to variations in the frequency of device use among family members. If so, it is inevitable that using multiple devices by multiple users can lead to difficulty maintaining situation awareness. Therefore, to relieve such interaction problems caused by the presence of co-users, we examined the effect of spontaneous visuospatial perspective taking on situation awareness with respect to the smart home interface. To this end, we measured whether merely the affordance of other users can elicit spontaneous visuospatial perspective-taking, replicating previous research. We also examined whether the affordances of other users can help enhance situation awareness in the mock-up smart home interface design we created. When participants adopted affordances of other users’ perspectives, they could easily perceive the information about the devices. Further, if they view the smart home interface through the affordances of other users’ perspectives, they better understood the status of devices only for devices frequently used by the other user. However, when they viewed the devices from other’s perspective, their understanding of devices mainly used by the self remained relatively low. Potential reasons for these findings are discussed along with proposals for future research.